Vitamin E reversed nicotine-induced toxic effects on bone biochemical markers in male rats - Mohamed , Norazlina; Hapidin, Hermizi; Othman , Faizah; Ahmad Shuid, Nazrun; Muhammad , Norliza; Soelaiman , Ima-Nirwana (2010)
Introduction: Vitamin E is beneficial in restoring bone histomorphometric parameters in nicotine-treated rats. This study determined the effectiveness of 3 forms of vitamin E in restoring bone metabolism in nicotine-treated rats. Material and methods: Thirty-five male Sprague-Dawley rats were divided into 5 groups: (1) control (C), (2) nicotine cessation (NC), (3) α-tocopherol (ATF), (4) tocotrienol-enhanced fraction (TEF) and (5) γ-tocotrienol (GTT). Treatment was carried out for 4 months. The control group was administered normal saline and olive oil throughout the treatment period while treatment for groups 2-5 was performed in 2 phases. In the first phase, the groups received nicotine 7 mg/kg intraperitoneally for 2 months. The following 2 months, group 2 received normal saline and olive oil while groups 3-5 received ATF, TEF or GTT, 60 mg/kg orally. Pre-treatment and post-treatment serum was collected for bone biochemical marker measurement using the ELISA method. Results: Nicotine increased serum bone-resorbing cytokines (interleukin-1 and interleukin-6) and the bone resorption marker pyridinoline (PYD) while reducing the bone formation marker osteocalcin after 2 months of nicotine treatment. The parameters failed to improve after nicotine was stopped for 2 months. Supplementation with the 3 forms of vitamin E improved the parameters, i.e. reduced the cytokines and pyridinoline as well as increased the osteocalcin. In addition, the TEF and GTT groups had a higher level of osteocalcin than the control group. Conclusions: Nicotine impaired bone metabolism and cessation of nicotine treatment did not reverse the effects. Vitamin E, especially the tocotrienols, restored bone metabolism that was impaired due to nicotine.